2023
DOI: 10.1021/acs.jafc.3c00657
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Insecticide/Calix[4]arene Complexes and Their Enhanced Insecticidal Activities againstPlutella xylostella

Abstract: Applications of supramolecular materials in plant protection have attracted significant interest in recent years. To develop a feasible method to improve the efficacy and reduce the usage of chemical pesticides, the effect of calix[4]­arene (C4A) inclusion on enhancing the insecticidal activity of commercial insecticides was investigated. Results showed that all three tested insecticides (chlorfenapyr, indoxacarb, and abamectin) with distinct molecular sizes and modes of action were able to form stable 1:1 hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In China, the management and crop losses are estimated to be about $0.77 billion per year . The abuse of conventional pesticides not only has harmful effects on the environment but also leads to the development of drug-resistant populations of P. xylostella . Azadirachtin A, found in plants, is used worldwide in agriculture and pest management for its insecticidal properties. Its popular application indicated that natural insecticides have the potential to be practical substitutes for synthetic pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the management and crop losses are estimated to be about $0.77 billion per year . The abuse of conventional pesticides not only has harmful effects on the environment but also leads to the development of drug-resistant populations of P. xylostella . Azadirachtin A, found in plants, is used worldwide in agriculture and pest management for its insecticidal properties. Its popular application indicated that natural insecticides have the potential to be practical substitutes for synthetic pesticides.…”
Section: Introductionmentioning
confidence: 99%